2015
DOI: 10.1016/bs.mie.2015.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic Models of G-Quadruplex Structures

Abstract: G-quadruplexes are noncannonical four-stranded DNA or RNA structures formed by guanine-rich repeating sequences. Guanines nucleotides can hydrogen bond to form a planar tetrad structure. Such tetrads can stack to form quadruplexes of various molecularities with a variety of types of single-stranded loops joining the tetrads. High-resolution structures may be obtained by X-ray crystallography or NMR spectroscopy for quadruplexes formed by short (≈25 nt) sequences but these methods have yet to succeed in charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
2

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 27 publications
4
27
0
Order By: Relevance
“…These studies are underway in our laboratory. We have carefully characterized the structures of long telomeric sequences (17,(38)(39)(40) by molecular dynamics simulations and experimental biophysical studies and have shown that for lengths up to 196 nt they always fold into structures containing the maximal number of possible G4 units, with no single-stranded gaps longer than 3 nt. POT1 would thus encounter an ordered array of G4 structures as a binding substrate in these longer sequences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies are underway in our laboratory. We have carefully characterized the structures of long telomeric sequences (17,(38)(39)(40) by molecular dynamics simulations and experimental biophysical studies and have shown that for lengths up to 196 nt they always fold into structures containing the maximal number of possible G4 units, with no single-stranded gaps longer than 3 nt. POT1 would thus encounter an ordered array of G4 structures as a binding substrate in these longer sequences.…”
Section: Discussionmentioning
confidence: 99%
“…A second study from the Wang and Opresko laboratories used single-molecule atomic force microscopy (AFM) to monitor POT1 binding to longer telomeric G4 structures and proposed a different model (16). In contrast to our published observations that long telomeric DNA always form structures with the maximal number of quadruplex units (17), they reported that none of the sequences they studied by AFM were fully folded to form the maximal number of G4 units (16). POT1 appeared to bind to single-stranded gaps between quadruplex units.…”
Section: Mechanism Of Pot1 Unfolding Of Telomeric Quadruplexesmentioning
confidence: 92%
“…[5] Sample homogeneity was confirmed by sedimentation velocity experiments as previously described. [6] [7] In only one case (sample 186D) was significant heterogeneity observed, requiring additional purification by HPLC methods developed and reported by our laboratory. [8] …”
mentioning
confidence: 99%
“…[5] Sample homogeneity was confirmed by sedimentation velocity experiments as previously described. [6,7] In only one case (sample 186D) was significant heterogeneity observed, requiring additional purification by HPLC methods developed and reported by our laboratory. [8] Figure 1A shows the CD spectra obtained for the quadruplex library (these spectra are provided in digital form as an Excel file in the Supporting Information).…”
mentioning
confidence: 99%